2002
DOI: 10.1038/oby.2002.106
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ghrelin Polymorphisms in Obesity Based on Three Different Studies

Abstract: Res. 2002;10: 782-791. Objective: Associations between preproghrelin DNA variants and obesity-related phenotypes were studied in 3004 subjects from the Québec Family Study (QFS), the HERI-TAGE Family Study (HERITAGE), and the Swedish Obese Subjects (SOS) Study. Research Methods and Procedures: Body mass index (BMI), fat mass (FM) from underwater weighing, and abdominal fat from computerized tomography were measured. The ghrelin polymorphisms were identified by polymerase chain reaction. Results: Arg51Gln QFS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
103
9
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(124 citation statements)
references
References 38 publications
11
103
9
1
Order By: Relevance
“…It has been demonstrated that Preproghrelin Leu72Met variant and obesity M Kuzuya et al the frequency of the 72Met allele of the preproghrelin gene is approximately 8% in the Caucasian population and approximately 2% in the black population in three different cohorts. 10 Compared with these previous studies, the frequency of the 72Met allele in our Japanese cohort was much higher than that observed in Caucasian or African populations, probably reflecting genetic/ethnic heterogeneity. The Leu72Met polymorphism of preproghrelin was previously found in a group of obese French children and adolescents.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…It has been demonstrated that Preproghrelin Leu72Met variant and obesity M Kuzuya et al the frequency of the 72Met allele of the preproghrelin gene is approximately 8% in the Caucasian population and approximately 2% in the black population in three different cohorts. 10 Compared with these previous studies, the frequency of the 72Met allele in our Japanese cohort was much higher than that observed in Caucasian or African populations, probably reflecting genetic/ethnic heterogeneity. The Leu72Met polymorphism of preproghrelin was previously found in a group of obese French children and adolescents.…”
Section: Discussioncontrasting
confidence: 89%
“…It has been reported that Leu72Met polymorphism is associated with triglyceride or lipoprotein (a) levels. 10,17 In the present study, however, we observed no association between serum lipid levels, fasting glucose, insulin, HbA1c or HOMA-IR levels and preproghrelin Leu72Met genotypes.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, the above findings could not be reproduced by other studies (Bing et al, 2005;Hinney et al, 2002;Jo et al, 2005;Zhu et al, 2010). Furthermore, one study of 3004 subjects even reported the Leu72Met polymorphism to be protective against fat accumulation; the polymorphism was related to lower BMI, fat mass and reduced visceral fat (Ukkola et al, 2002). Another study suggests that Leu72 allele carriers are more prone to weight variability in response to environmental factors given the reduced frequency of Leu72Met polymorphism in monozygotic twins discordant for obesity (Leskela et al, 2009).…”
Section: Common Genetic Variations Of Ghrl and Ghs-r Genes In Human Omentioning
confidence: 80%
“…Relationships have been described between obesity and genomic variants of the ghrelin (GHRL) (Gueorguiev et al, 2009;Korbonits et al, 2002;Kuzuya et al, 2006;Leskela et al, 2009;Miraglia Del et al, 2004;Ukkola et al, 2001;Ukkola et al, 2002) M a n u s c r i p t 12 and ghrelin receptor (GHS-R) (Baessler et al, 2005;Gueorguiev et al, 2009;Liu et al, 2007) genes.…”
Section: Common Genetic Variations Of Ghrl and Ghs-r Genes In Human Omentioning
confidence: 99%